2010
DOI: 10.1074/jbc.m110.115147
|View full text |Cite
|
Sign up to set email alerts
|

Apobec-1 Complementation Factor Modulates Liver Regeneration by Post-transcriptional Regulation of Interleukin-6 mRNA Stability

Abstract: Apobec-1 complementation factor (ACF) is the RNA binding subunit of a core complex that mediates C to U RNA editing of apolipoprotein B (apoB) mRNA. Targeted deletion of the murine Acf gene is early embryonic lethal and Acf ؊/؊ blastocysts fail to implant and proliferate, suggesting that ACF plays a key role in cell growth and differentiation. Here we demonstrate that heterozygous Acf ؉/؊ mice exhibit decreased proliferation and impaired liver mass restitution following partial hepatectomy (PH). To pursue the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…S3). Staining in the liver was strong in both cytoplasm and nucleus at P0 and P21 but was largely circumscribed within nucleus of hepatocytes in adults, in accordance with previous studies (76,78). Similarly, weak expression of A1CF in muscle (76) was confirmed at all time points in our study (Fig.…”
Section: A1cfsupporting
confidence: 81%
“…S3). Staining in the liver was strong in both cytoplasm and nucleus at P0 and P21 but was largely circumscribed within nucleus of hepatocytes in adults, in accordance with previous studies (76,78). Similarly, weak expression of A1CF in muscle (76) was confirmed at all time points in our study (Fig.…”
Section: A1cfsupporting
confidence: 81%
“…Other work has examined the parallel possibility that alternate (non-apoB RNA) targets exist for ACF, particularly in view of the observation that germline deletion of ACF is early embryonic lethal (18). These findings were extended recently with the finding that ACF modulates cytokine (specifically interleukin 6) mRNA stability (20). Taken together, the findings suggest that apobec-1 and ACF each have a range of targets distinct from apoB mRNA, whose biological implications have yet to be formally defined.…”
Section: Lipoprotein Assembly Vectorial Transport and Secretionmentioning
confidence: 58%
“…This report does not represent the first suggestion that A1CF may be important in nonediting-related RNA biology. In hepatic cells, A1CF has been shown to regulate both the stability (Blanc et al 2010) and the subcellular localization of specific mRNAs (Galloway et al 2010). Additional work demonstrated that A1CF behaves as a nuclear shuttling protein (Blanc et al 2003), and the shuttling is mediated by its interaction with APOBEC1 (Chester et al 2003).…”
Section: Discussionmentioning
confidence: 99%